Six Years of European Visual Climate Activism: A Longitudinal Analysis of Fridays for Future and Extinction Rebellion’s Online Visual Communication - Costanza, Azzuppardi; Nicole, Doerr; Langa, Maria; Magnani, Matteo; Dániel, Oross; Rossi, Luca; Segerberg, Alexandra; Uba, Katrin; Arminio, Luigi (AoIR Selected Papers of Internet Research, 2026)
This paper addresses how global climate movements use images in their social media communication from a comparative perspective: How have Fridays For Future and Extinction Rebellion in Italy, Germany, Sweden and Hungary evolved their use of visual communication on Instagram between 2018 and 2024? We argue that three lines of analysis are important for a comprehensive understanding of the relation between image content and protest movements: a) complementary movements, b) complementary countries and c) longitudinal observation. We explore those lines of analysis by leveraging a mixed-method analysis of full production of images shared by FFF and XR on Instagram in the period 2018-2024.